Effect of Nigella sativa Intake on Oxidative Stress and Inflammation in Patients with Metabolic Syndrome and Related Disorders: A Systematic Review and Meta-analysis of Randomized Controlled Trials - Hosseini, Hossein; Ghavidel, Farideh; Aliyari, Mahdieh; Hashemy, Seyed I.; Jamialahmadi, Tannaz; Sahebkar, Amirhossein (Current Pharmaceutical Biotechnology, 2024)
Background: Several studies have shown that the intake of N. sativa has a beneficial effect on metabolic syndrome and related disorders. In this meta-analysis, our primary objective was to assess the impact of Nigella sativa consumption on inflammation and oxidative stress biomarkers among individuals diagnosed with metabolic syndrome and its associated conditions. Methods: Our search was conducted on prominent online databases such as Web of Science, Scopus, PubMed, and EMBASE, utilizing relevant keywords until August 2023. Results: This meta-analysis was performed on 16 RCTs comprising 1033 participants. Our results showed that intake of Nigella sativa significantly decreased CRP (SMD: -0.60; (95% CI: from -0.96 to -0.23); P = 0.00), TNF-α (SMD: -0.53; (95% CI: from -0.74 to -0.53); P = 0.00); IL-6 (SMD: -0.54 ; (95% CI: from -1.01 to -0.07); P = 0.02), and MDA: (SMD: -1.28; (95% CI: from -2.11 to -0.46); P = 0.00) levels. In addition, SOD: (SMD: 1.35; (95% CI, from 0.77 to 1.93); P = 0.00) and TAC (SMD: 2.82; (95% CI, from 0.55 to 5.084); P = 0.01) levels significantly increased in the intervention group compared to the placebo group. Conclusion: Our results showed that THE consumption of N. sativa could be associated with improved oxidative stress and inflammation in patients with metabolic syndrome and related disorders.
Keywords: meta-analysis